LITERATURE REVIEW: DILEMA ETIS DAN LEGAL DALAM PENERAPAN TEKNOLOGI MEDIS DALAM PERAWATAN PASIEN - Kasenda, Edson; Mambu, Ian Ruddy (Klabat Journal of Nursing, 2025)
Background: The application of medical technology in patient care, such as telemedicine, artificial intelligence (AI), and robotics, provides convenience and improves access to health services. However, this technology also raises ethical and legal challenges related to data privacy, algorithmic bias, and the responsibility of health professionals. Objective: To identify and understand the ethical and legal dilemmas that arise in the application of medical technology. Methods: Descriptive analysis with a literature review approach of publications from 2015 to 2025. Searches were conducted on PubMed, Scopus, ScienceDirect, and Google Scholar using relevant keywords. Inclusion criteria: original research articles or peer-reviewed reviews, full-text manuscripts, Indonesian/English language, and discussing ethical/legal dilemmas in the application of medical technology in clinical practice. Exclusion criteria: editorials/opinions/short comments, non-peer-reviewed proceedings, non-health studies, duplicates, and articles outside the year range. Results: Many health professionals feel unprepared to face the ethical dilemmas that arise; while a number of policies, especially in developing countries, are not yet fully adequate to address these challenges. Conclusion: There is a need to develop ethical guidelines, adaptive legal frameworks, and training programs for healthcare professionals to support the fair and safe application of medical technology. Latar Belakang: Penerapan teknologi medis dalam perawatan pasien, seperti telemedicine, kecerdasan buatan (AI), dan robotika, memberikan kemudahan dan meningkatkan akses layanan kesehatan. Namun, teknologi ini juga menimbulkan tantangan etis dan legal terkait privasi data, bias algoritma, dan tanggung jawab profesional kesehatan. Tujuan: Mengidentifikasi serta memahami dilema etis dan hukum yang muncul dalam penerapan teknologi medis. Metode: Analisis deskriptif dengan pendekatan tinjauan pustaka terhadap publikasi 2015–2025. Pencarian dilakukan pada PubMed, Scopus, ScienceDirect, dan Google Scholar menggunakan kata kunci yang relevan. Kriteria inklusi: artikel penelitian asli atau tinjauan yang melalui peer review, naskah full-text, bahasa Indonesia/Inggris, dan membahas dilema etis/ legal penerapan teknologi medis pada praktik klinis. Kriteria eksklusi: editorial/opini/komentar singkat, prosiding tanpa peer review, studi non-kesehatan, duplikasi, dan artikel di luar rentang tahun. Hasil: Banyak profesional kesehatan merasa tidak siap menghadapi dilema etis yang muncul; sementara sejumlah kebijakan, terutama di negara berkembang, belum sepenuhnya memadai untuk menjawab tantangan ini. Kesimpulan: Diperlukan pengembangan pedoman etis, kerangka hukum yang adaptif, serta program pelatihan bagi profesional kesehatan untuk mendukung penerapan teknologi medis yang adil dan aman.